Photocatalyst Activity of TiO2/CQD Nanocomposite for Degradating Pesticide Contaminants in Water - Bt. Sunardi, Asrianti; Candra Kirana, Kurnia Galuh; Mufti, Nandang; Wisodo, Hari (Universitas Negeri Malang, 2023)
This study investigates the effectiveness of TiO2/CQD composites on the pesticide degradation. TiO2/CQD composites has been successfully synthesized using hydrothermal methods. The samples were characterized by XRD, TEM, PL, BET, and UV-Vis. The result of XRD shows the addition of CQD does not affect the crystal phase of TiO2. The result of TEM shows that CQD are well deposited on the TiO2 surface. The particle size of the TiO2/CQD composite is getting larger after the addition of CQD compared to pure TiO2 and the average particle size distribution is about 109-114 nm. PL analysis found that the addition of CQD increased the intensity of NBE emissions while Tii decreased. The BET test result of the TiO2/CQD composite shows a surface area of 8.6710 m2/g. The pore diameter is 37.4 nm compared to pure TiO2. While the pore volume is 0.0754 cm3/g. Photocatalyst activity of TiO2/CQD against pesticides after 150 minutes of irradiation reached 89.9667%. TiO2/CQD photocatalyst has significant potential for pesticide water treatment. Further research is needed for large-scale optimization and evaluation.